Cybrids and tetrad sterility for developing true potato seed hybrids - Golmirzaie, A.M.; Tenorio, J.; Serquén, F.; Ortíz, R. (Wiley, 2003)
Potato cybrids result from the fusion between cytoplasm and nuclear gene donors. Such genetic materials are an alternative means to broaden the breeding pool by non-sexual gene transfer. Tetrad pollen sterility provides also another source of male sterility with some potential for true potato seed breeding. The objective of this research was to investigate cybrid-derived offspring for both agronomic and reproductive characteristics in two contrasting Peruvian locations, and to examine new exotic germplasm for tetrad sterility, with the aim of broadening the breeding pool available at the Centro Internacional de la Papa (CIP). The cybrids were derived from fusions between Y-245.7, a clone with tetrad sterility, and Atzimba. These cybrids were crossed with selected male parents from the CIP breeding population, and their hybrid offspring were tested in La Molina (coastal desert) and Huancayo (cool highlands). In addition, other clones with tetrad sterility were also crossed with selected testers to determine their breeding value. There were significant differences for tuber yield, style length, and berry number among the hybrid offspring, and the genotype by environment interaction was significant for tuber yield and berry number. The top 25% highest yielding cybrid-derived offspring across both locations showed the same tuber yield although they were significantly different for some of the reproductive characteristics. With the exception of one cybrid, the others did not exhibit segregation for tetrad sterility in their hybrid offspring, which were male fertile. However, the offspring derived from crosses between other sources of tetrad sterility and the same testers all showed tetrad sterility, and some of them had outstanding tuber yield at La Molina. The lack of segregation for tetrad sterility in these new crosses suggests that the non-cybrid, male sterile, female parents are triplex or quadriplex for the Tr nuclear locus, which interacts with a sensitive cytoplasm (e.g. Trs from S. verrucosum or S. stoloniferum) to produce tetrad sterility in potato.